PEDULI LINGKUNGAN MELALUI PROGRAM KEGIATAN MEMILAH SAMPAH DI SDN SUKABUMI 2 PROBOLINGGO - Ani Anjarwati; Afi fa; Ilmia Mia; Desvita Sania Putri; Muhammad Sulthan Bayu Santoso (JGK (Jurnal Guru Kita), 2022)
This article is a research article related to waste management for elementary school children, one of which is through Tri Bakti Counseling activities by Panca environment, namely the waste sorting activity program at SDN Sukabumi 2. The purpose of this activity is to foster a sense of concern children to the surrounding environment by disposing of garbage in its place. The method used in this study is a qualitative method, where this method emphasizes the aspect of understanding students in depth about the problem of waste, types of waste and how to manage waste properly and correctly which has been carried out at SDN Sukabumi 2. This activity was carried out for 3 years. day with a total of 40 students consisting of 4th and 5th graders. The conclusion of the waste sorting program conducted at SDN Sukabumi 2 is to implement environmental hygiene awareness education at the elementary school level as a form of love for nature.